Globalization and social determinants of health: Introduction and methodological background (part 1 of 3) - Schrecker Ted; Labonté Ronald (BMC, 2007)
Abstract Globalization is a key context for the study of social determinants of health (SDH). Broadly stated, SDH are the conditions in which people live and work, and that affect their opportunities to lead healthy lives. In this first article of a three-part series, we describe the origins of the series in work conducted for the Globalization Knowledge Network of the World Health Organization's Commission on Social Determinants of Health and in the Commission's specific concern with health equity. We explain our rationale for defining globalization with reference to the emergence of a global marketplace, and the economic and political choices that have facilitated that emergence. We identify a number of conceptual milestones in studying the relation between globalization and SDH over the period 1987-2005, and then show that because globalization comprises multiple, interacting policy dynamics, reliance on evidence from multiple disciplines (transdisciplinarity) and research methodologies is required. So, too, is explicit recognition of the uncertainties associated with linking globalization - the quintessential "upstream" variable - with changes in SDH and in health outcomes.